2015
DOI: 10.1063/1.4915301
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected bismuth concentration profiles in metal-organic vapor phase epitaxy-grown Ga(As1−xBix)/GaAs superlattices revealed by Z-contrast scanning transmission electron microscopy imaging

Abstract: A set of GaAs1−xBix/GaAs multilayer quantum-well structures was deposited by metal-organic vapor phase epitaxy at 390 °C and 420 °C. The precursor fluxes were introduced with the intent of growing discrete and compositionally uniform GaAs1−xBix well and GaAs barrier layers in the epitaxial films. High-resolution high-angle annular-dark-field (or “Z-contrast”) scanning transmission electron microscopy imaging revealed concentration profiles that were periodic in the growth direction, but far more complicated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 18 publications
(25 reference statements)
1
11
0
Order By: Relevance
“…b). Considering our previous TEM studies, the first Bi spike in each period is associated with the Bi source flux into the growth system, resulting in the growth of the GaAs 1‐ y Bi y layer. Based on the observation with the growth of GaAs 1‐ y Bi y single layers using the TEBi source (Sample E1 in Table ), it is expected that there will be some residual Bi on the GaAs 1‐ y Bi y film surface.…”
Section: Resultsmentioning
confidence: 97%
“…b). Considering our previous TEM studies, the first Bi spike in each period is associated with the Bi source flux into the growth system, resulting in the growth of the GaAs 1‐ y Bi y layer. Based on the observation with the growth of GaAs 1‐ y Bi y single layers using the TEBi source (Sample E1 in Table ), it is expected that there will be some residual Bi on the GaAs 1‐ y Bi y film surface.…”
Section: Resultsmentioning
confidence: 97%
“…The sample designs included a thick (43.5 nm) motif SL composed of five repetitions of In 0.37 Al 0.63 As (20.1 nm)/In 0.67 Ga 0.33 As (23.4 nm) with 1% tensile/compressive strain relative to the InP substrate, nominally and respectively, and a thin (4.1 nm)-motif SL composed of 124 repetitions of In 0.44 Al 0.56 As (1.9 nm)/In 0.6 Ga 0.4 As (2.2 nm) nominally strained +0.56%/−0.47% relative to the substrate, respectively. However, they provide rather little insight into the composition profile within the motif, which is critical to device performance, as the same high-resolution X-ray diffraction (HRXRD) data typically can be fit with the same accuracy with several composition profiles that have the same periodicity and average composition as the sample [3]. Transmission electron microscopy (TEM) provides details of the atomic structures of the layers and interfaces, most readily in 2D projections [4].…”
Section: Methodsmentioning
confidence: 99%
“…These simulations can provide an accurate measurement of the periodicity of the SL and the composition of the motif averaged over its volume. However, they provide rather little insight into the composition profile within the motif, which is critical to device performance, as the same high-resolution X-ray diffraction (HRXRD) data typically can be fit with the same accuracy with several composition profiles that have the same periodicity and average composition as the sample [3].…”
Section: Introductionmentioning
confidence: 99%
“…In order to grow high-quality epitaxial GaAs 1-x Bi x with uniform Bi concentration, we need to understand how Bi atoms are incorporated in the growth front and subsequently distributed in the grown films. X-ray diffraction (XRD) and high-angle annular dark-field (HAADF) scanning transmission electron microscopy (STEM) have been used previously [15] to investigate the Bi concentration profile in the GaAs 1-x Bi x /GaAs superlattice investigated in this study. The XRD method allows deduction of the Bi concentration in the layers that comprise the superlattice, but it is based on fitting the diffraction pattern to a simulation for which the generic shape of the concentration profile is an input.…”
Section: Introductionmentioning
confidence: 99%
“…Often the square wave form of a perfect superlattice is assumed. In the previous study [15], the shape of the concentration profile was deduced from HAADF-STEM ("Z-contrast") images, rather than assumed, to refine the concentration determination. In APT studies of GaAs and GaAs-based materials have been reported as well [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%